2015
DOI: 10.1210/en.2015-1077
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposures of Male Rats to the Environmental Chemicals Bisphenol A and Di(2-Ethylhexyl) Phthalate Impact the Sexual Differentiation Process

Abstract: The increasing incidence of reproductive anomalies, described as testicular dysgenesis syndrome, is thought to be related to the exposure of the population to chemicals in the environment. Bisphenol A (BPA) and di(2-ethylhexyl)phthalate (DEHP), which have hormonal and antihormonal activity, have attracted public attention due to their presence in consumer products. The present study investigated the effects of BPA and DEHP on reproductive development. Timed-pregnant female rats were exposed to BPA and DEHP by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…Only two previous animal studies have examined the relationship between BPA exposure and global DNA hydroxymethylation, where maternal exposure to BPA inhibited global DNA hydroxymethylation in adult rat testis and BPA exposure led to a decrease of testicular TETs and 5hmC levels in Gobiocypris rarus testes [26]. 5hmC density and function appears to vary with cell type, differentiation stage and gene specific function [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two previous animal studies have examined the relationship between BPA exposure and global DNA hydroxymethylation, where maternal exposure to BPA inhibited global DNA hydroxymethylation in adult rat testis and BPA exposure led to a decrease of testicular TETs and 5hmC levels in Gobiocypris rarus testes [26]. 5hmC density and function appears to vary with cell type, differentiation stage and gene specific function [38].…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of 5hmC is potentially crucial for regulation of gene expression during spermatogenesis [25]. While two recent animal studies suggested that exposure to BPA inhibited global DNA hydroxymethylation or TETs-mediated DNA demethylation [26,27], little information is available about the effect of BPA exposure on global 5hmC in humans.…”
Section: Introductionmentioning
confidence: 99%
“…BPA exposure induces DNA methylation and histone protein modifications in the brain and other organs [72; 114; 115; 116; 117; 118; 119; 120; 121]. The expression of miRNAs in the placenta, liver, and likely other organs, including the brain, can also be influenced by BPA [122; 123; 124; 125].…”
Section: Overall Conclusionmentioning
confidence: 99%
“…Altered cellular function occurring at low‐dose chemical exposures is more apt to result from receptor–ligand interactions than exposures occurring at high doses that cause cellular damage and overt toxicity. Therefore, we used a biologically based response model of low‐dose exposure paradigms of BPA at 2.5 or 25 and DEHP at 5 or 50 μg/kg bw (Abdel‐Maksoud et al ., ). Timed‐pregnant Long‐Evans dams (Harlan‐Teklad, Indianapolis, IN, USA) were grouped into four groups.…”
Section: Methodsmentioning
confidence: 97%